Developing Capacities for Implementing the Water-Energy-Food Nexus - Czunyi Sarah (Change and Adaptation in Socio-Ecological Systems, 2015)
The novelty of the W-E-F nexus approach, given that it requires new coordination mechanisms within and between institutions and disciplines, requires new forms and types of capacities in order to be effective. This paper identifies some of the existing capacity gaps and measures to address those gaps, in order to ensure a successful implementation of the W-E-F nexus approach. Capacity development for the nexus requires a variety of mechanisms from the individual to institutional levels. To successfully put the W-E-F nexus into practice we should build on the strengths of existing mechanisms, while also improving coordination and integration of seemingly divergent approaches in the water, energy, and food sectors. Capacity development within and between sectors will be key to a successful implementation of the W-E-F nexus approach.